Cameroon : Staff Report for the 2001 Article IV Consultation, First Review of the First Annual Program Under the Poverty Reduction and Growth Facility, and Request for a Waiver and Modification of Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Cameroon's good record of performance in the macroeconomic and structural areas under the previous three-year Poverty Reduction and Growth Facility (PRGF) arrangement remained broadly satisfactory during the first six months of the first annual program. Progress in structural reforms has continued, notably in the financial, transport, forestry, and petroleum sectors. For the medium term, Executive Directors emphasized the importance of continuing to strengthen the efficiency and transparency of public revenue and expenditure management, and welcomed the authorities' intention to launch a technical audit of the judicial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet